Stability of Encapsulated Vitamin C in Modified Cassava Flour (MOCAF)-Based Composite Noodles - Resti Pranata Putri; Nadiyah Zuhroh; Nadhifah Al Indis; Annisa'U Choirun; Amellia Dwi Rizkyana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This study evaluated the effect of Modified Cassava Flour (MOCAF) substitution on the stability of encapsulated vitamin C (ascorbic acid), crude fiber content, and color index of starch-based composite noodles. Vitamin C was encapsulated using a maltodextrin–CMC matrix (18.2:1.8%) via freeze-drying and incorporated into noodles with varying wheat-to-MOCAF ratios: MCF00 (100:0), MCF01 (90:10), MCF02 (70:30), and MCF03 (50:50). These were compared with Control 1 (unfortified) and Control 2 (fortified with non-encapsulated vitamin C). Encapsulation significantly improved vitamin C retention, reaching 0.32–0.38 mg/g, approximately twofold higher than the non-encapsulated control (0.15 mg/g). Thermal processing caused a marked decline in the Modified Noodle Color Index (NCIm) of Control 2 (62.67 to 51.44), likely due to Maillard-like browning reactions. In contrast, noodles with encapsulated vitamin C maintained a stable color (NCIm 61.06 to 63.44). Increasing MOCAF substitution significantly enhanced crude fiber content (up to 4.97% in MCF03) and improved noodle lightness (L*). Overall, the maltodextrin–CMC system effectively protected vitamin C from thermal degradation, regardless of starch matrix variation. Further studies are recommended to investigate shelf-life stability and in vitro release of vitamin C in the gastrointestinal tract.